The Impact of Foreign Direct Investment on Domestic Investment: Evidence from Sudan - Yahia, Yassin Elshain; Haiyun, Liu; Khan, Muhammad Asif; Shah, Sayyed Sadaqat Hussain; Islam, Mollah Aminul (International Journal of Economics and Financial Issues, 2018)
This study applies the ARDL Bounds test to cointegration and Granger Causality to examine the impact of foreign direct investment (FDI) inflows on domestic investment of Sudan over the period 1976-2016. Empirical results show a crowd out effect of FDI on Sudan’s domestic investment, and the results confirm the cointegration relationships. Economic growth, exchange rate, macroeconomic stability and natural resource rent have shown short and long-run significant association with domestic investment, whereas, foreign direct investment appears as a long-term determinant. Moreover, the ECM reveals that system corrects previous period disequilibrium at an annual rate of 35%. The Granger Causality results conclude unidirectional causal flows from FDI, exchange rate, macroeconomic stability, natural resource rent, and trade openness to domestic investment. The study suggests some policy measures to design effective policies for macroeconomic stability; controlling inflation, flexible exchange rate spurring economic growth, and as well as developing effective strategies to encourage the mode of FDI that can create technological and market share spillover. Keywords: FDI, Domestic Investment, crowd-in, crowd-out JEL Classifications: E22; F23; O55 DOI: https://doi.org/10.32479/ijefi.6895